2017
DOI: 10.1001/jamafacial.2016.1038
|View full text |Cite
|
Sign up to set email alerts
|

Management Controversies in Head and Neck Melanoma

Abstract: Dr Zenga had full access to all of the data in the study and takes responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…44,45 Management follows the same principles as for nonhead and neck melanoma. 46 Breslow thickness of the SM gives instructions for the excision margins. Surgery should be performed with resection margins, as for other cutaneous melanomas.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 Management follows the same principles as for nonhead and neck melanoma. 46 Breslow thickness of the SM gives instructions for the excision margins. Surgery should be performed with resection margins, as for other cutaneous melanomas.…”
Section: Managementmentioning
confidence: 99%
“…Rarely flap coverage is required, especially in defects where the bony skull has also been removed 49 (many studies compared narrow (1 or 2 cm) to wide (3-5 cm)) margins, and none of these identified a difference in local recurrence or overall survival between the narrow or wide margin groups. [43][44][45][46] One study, however, found a significant increase in regional recurrence for narrow margins for patients with melanoma thicker than 2 mm, while for thin melanoma, excision margins of less than 1 cm increased the risk of local recurrence. 50…”
Section: Managementmentioning
confidence: 99%
“…The article by Zenga et al 1 in this issue of JAMA Facial Plastic Surgery is a timely addition to the literature for those clinicians who treat patients with pigmented lesions of the face, scalp, and neck. While many of the brown lesions we see in our practices will be benign, the incidence of melanoma is increasing.…”
Section: Invited Commentarymentioning
confidence: 99%
“…A recent systemic review on the management controversies of head and neck melanoma published by Zenga et al showed level 4 evidence supporting delayed reconstruction. The authors cited that existing studies could not identify factors predictive of positive margins and therefore advocated that immediate reconstruction be limited to low‐risk lesions amenable to primary closure …”
Section: Introductionmentioning
confidence: 99%
“…The authors cited that existing studies could not identify factors predictive of positive margins and therefore advocated that immediate reconstruction be limited to low-risk lesions amenable to primary closure. 9 To address this controversy, a systematic review of the literature was undertaken to examine the oncologic outcomes, specifically, the rates of positive margins and local recurrence, that are associated with the immediate versus delayed reconstruction of cutaneous melanoma in the head and neck region.…”
Section: Introductionmentioning
confidence: 99%